Epidemiological study of ticks harbouring Aeromonas hydrophila in areas endemic and non‐endemic to Japanese‐spotted fever. Issue 2 (5th January 2023) - Kondo, Makoto; Matsushima, Yoshiaki; Nakanishi, Takehisa; Iida, Shohei; Habe, Koji; Yamanaka, Keiichi
Abstract: Objectives: Aeromonas spp. often cause life‐threatening diseases, including necrotizing fasciitis, which may lead to septic shock and ultimately death. Aeromonas infections are believed to be transmitted via minor wounds or the consumption of fresh fish. However, after the detection of Aeromonas hydrophila in ticks in areas endemic to Japanese‐spotted fever (JSF), a novel transmission route of A. hydrophila (i.e., via tick bites) has been proposed. We investigated the prevalence of A. hydrophila in ticks in areas endemic and not endemic to JSF in the Mie Prefecture, Japan. Methods: We collected ticks from endemic and nonendemic areas in summer and winter and assessed them for presence of A. hydrophila using polymerase chain reaction. Results: Six A. hydrophila isolates were obtained from 95 ticks in endemic areas, whereas one A. hydrophila isolate was obtained from 142 ticks in non‐endemic areas, in summer. All ticks that harboured A. hydrophila were Haemaphysalis longicornis (H.L); these ticks were almost at the larval stage and also carried Rickettsia spp. in the endemic area. In contrast, 51 and 41 ticks in the endemic and non‐endemic areas were captured in winter, respectively; A. hydrophila was not detected in these. Conclusions: This study revealed the prevalence of tick‐borne A. hydrophila . Therefore, the risk of transmission of A. hydrophila via a tick bite should be considered in the following conditions: areas abundant in H. L. harbouring Rickettsia spp., in areas endemic for JSF, presence of ticks in the larval stage and during the summer season.